Méthodologie de simulation d’impact sur un bâtiment industriel en béton armé - Moulin, Stéphane; Koechlin, Pierre; Potapov, Serguei; Champain, Eric (European Journal of Computational Mechanics, 2004)
In the context of nuclear projects, Electricité de France (EDF) studies the mechanical consequences of impact loads on reinforced concrete shell structures. We developed a numerical methodology to simulate this kind of accident. Both local behaviour in the impact zone and vibration of the whole structure are treated simultaneously even if they belong to different fields: during impact, the local behaviour is a fast dynamics issue whereas the structure shaking is a slow dynamics linear problem. To treat the physical phenomena, our modelling strategy is based on a domain decomposition method implemented into EUROPLEXUS fast dynamics software. The non-linear local behaviour is described by a material law, which uses resultant shell variables and accounts for plasticity and damage.